INFLUENCE OF THE SCALE EFFECT UPON THE FINANCIAL RESULTS OF THE BANKS IN BULGARIA - Z. V. Vatev (Финансы: теория и практика, 2017)
The object of attention in the article is the profitability and efficiency of the banks in Republic of Bulgaria. The subject of the development focuses onto the influence of the credit institutions size upon their financial results. The objective of this study is to either to reveal that there are sufficient grounds to believe that the effect of the scale renders its influence upon the profitability and efficiency indicators or such a dependency can hardly be found. This study comprises observations about the processes in the banking sector of the country for the period 2007–2016. A coefficient analysis was employed, using a system of indicators suitably selected to this end. Certain dependency between the size of the banks in Bulgaria and the values of these financial indicators was established on the basis of the analysis of the real empirical data. It was concluded that utilizing the scale effect influence the large credit institutions manage to derive certain advantages in comparison to the smaller in size banks. The idea that by means of further consolidation of the banking sector of the country its efficiency can be increased, was substantiated.